(NsTIHOTWORENIQ I PO\MY (B/s - (NlERMONTOW(B, (NmIHAIL `RXEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1980)
(Nw KNIGU WO[LI IZBRANNYE STIHOTWORENIQ m(B.(N`(B.(NlERMONTOWA(B, (NW BOLX[INSTWE SWOEM OTOBRANNYE DLQ PE^ATI SAMIM PO\TOM(B. (NkROME TOGO(B, (NW SBORNIK WKL@^ENY PO\MY(B: (S0(NpESNQ PRO CARQ iWANA wASILXEWI^A(B...(S1(B, (S0(NtAMBOWSKAQ KAZNA^EJ[A(S1(B, (S0(NbEGLEC(S1(B, (S0(NdEMON(S1 (NI (S0(NmCYRI(S1(B.s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\ZIQ(B, (NPO\MYs